2014
DOI: 10.1111/joms.12072
|View full text |Cite
|
Sign up to set email alerts
|

The Discursive Construction of Strategists' Subjectivities: Towards a Paradox Lens on Strategy

Abstract: Until recently, the field of strategy has neglected the question of what it means to be a strategist. Based on an analysis of 68 interviews with strategy practitioners, our results highlight four main tensions that emerge from strategists' discourses on strategizing work: the social tension, the cognitive tension, the focus tension, and the time tension. This tension-based representation of strategy enables us to differentiate between three forms of strategists' subjectivities, i.e. the ways by which strategis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 54 publications
0
88
0
3
Order By: Relevance
“…These practice-oriented studies have not focused on transcendence specifically (e.g., Beech et al, 2004;Dameron & Torset, 2014;Jarzabkowski et al, 2013;Michaud, 2014;Murninghan & Conlon, 1991), yet have suggested the complexity of such response, for example, by showing how practices that differentiate paradoxical poles can unfold alongside those that integrate them (Andriopoulos & Lewis, 2009;Knight & Paroutis, forthcoming;Smith, 2014). In addition, studies have begun to show that one particularly useful way to examine transcendence is to study rhetorical practices (Abdallah et al, 2011;Jarzabkowski & Sillince, 2007) and we will turn to this insight below.…”
Section: Theoretical Background Paradox Theory and Transcendencementioning
confidence: 99%
See 3 more Smart Citations
“…These practice-oriented studies have not focused on transcendence specifically (e.g., Beech et al, 2004;Dameron & Torset, 2014;Jarzabkowski et al, 2013;Michaud, 2014;Murninghan & Conlon, 1991), yet have suggested the complexity of such response, for example, by showing how practices that differentiate paradoxical poles can unfold alongside those that integrate them (Andriopoulos & Lewis, 2009;Knight & Paroutis, forthcoming;Smith, 2014). In addition, studies have begun to show that one particularly useful way to examine transcendence is to study rhetorical practices (Abdallah et al, 2011;Jarzabkowski & Sillince, 2007) and we will turn to this insight below.…”
Section: Theoretical Background Paradox Theory and Transcendencementioning
confidence: 99%
“…Paradoxes have been shown to emerge and be reflected within discourse and rhetoric (Dameron & Torset, 2014;Whittle et al, 2008) and specific discursive practices, such as ambiguity, have been shown to be a central means through which actors respond to paradox (Abdallah & Langley, 2013;Hatch & Erhlich, 1993;Jarzabkowski & Lê, forthcoming). Regarding transcendence specifically, Abdallah et al (2011) point to the discursive foundations of transcendence and explore important nonrhetorical mechanisms, such as groupthink, that support (and eventually undermine) transcendence.…”
Section: Rhetoric and Transcendencementioning
confidence: 99%
See 2 more Smart Citations
“…These everyday interactions bring paradoxes into being, giving them salience and invoking responses (Dameron & Torset, 2014;Spee & Jarzabkowski, 2011). We therefore focus in this paper on paradoxes of performing, which is where people experience paradox in their everyday roles (Smith &Lewis, 2011).…”
Section: Practice Lens: Ongoing Micro-responses To Paradoxmentioning
confidence: 99%